Exploring the dyad: the relationship establishment between a novice physical education teacher and his mentor. Issue 1 (1st January 2017) - Gordon, Evelyn J.
Abstract: The retention of new teachers is a noteworthy issue among physical education teachers. One way to combat attrition is with the implementation of induction programs that have a strong emphasis on mentoring. Mentoring creates a growth - in - connection for the novice physical education teacher as well as the mentor. The relational cultural theory (RCT) develops relationships based in situational boundaries between the mentor and the mentee. RCT explores the nature of human development based on the individuals involved in these relationships. The purpose of the study was to explore the perception of the relationship between a novice physical education teacher and his mentor and to determine if the mentoring relationship between the participants reflected the RCT model. Observations, interviews, and the researcher's journal were used as a means for data collection. In this study, meaningful relationships occurred in the working relationship, as well as the personal relationship. It was indicated that when meaningful relationships are established, novice physical education teachers are more confident in their teaching abilities and are more likely stay in the profession.